"There is a lot more potential" - practitioner perspectives on technology and data-driven talent identification, selection, and development in a German Bundesliga academy - Monsees, L. M. (International Journal of Sports Science and Coaching, 2024)
This case study explored the perceptions and utilisation of data-driven methods of coaches, scouts, and a sporting manager overseeing the U8-U14 unit of a German Bundesliga academy. It comprised seven semi-structured interviews and employed thematic analysis to unravel the complexities of talent identification, selection and development (TISD). The findings provide highly contextual insights into practices and perceptions of key stakeholders within the context of academy football. Technology and data-driven methods were restricted to anthropometric measurements and automated video evaluations. Nonetheless, informants recognised the potential of data-driven methods, such as AI, to enhance TISD practices and decision-making. Financial constraints did not pose a barrier, however, challenges, such as limited expertise and insufficient time for data interpretation, hindered the wider adoption of data-driven strategies and technologies. It is suggested that training staff in data interpretation and investing in skilled personnel could improve the effective use of new technologies and enhance player development. Legal regulations, such as the General Data Protection Regulations, were perceived as potential hurdles to adopt innovative methods. Moreover, demographic dynamics, particularly younger staff, are believed to positively influence technological adoption. The need for further research to explore how organisational dynamics and data protection laws impact the adoption and effectiveness of data-driven methods in football academies was suggested.